Aerodynamic and aeroacoustic performance assessment of a vertical axis wind turbine by synergistic effect of blowing and suction. (1st November 2022) - Liu, Qingsong; Miao, Weipao; Bashir, Musa; Xu, Zifei; Yu, Nanting; Luo, Shuai; Li, Chun
Highlights: An innovative active flow control method based on blowing and suction is proposed. The aerodynamic and noise characteristics are investigated by numerical simulations. The physical mechanisms of power enhancement and noise reduction are obtained. This active device is a promising solution for low-noise design for wind turbines. Abstract: The power efficiency of Darrieus wind turbines significantly deteriorates during rotation caused by periodic dynamic stall at low tip speed ratios. This leads to a strong fluctuation in torque and a reduction in energy acquisition. This paper aims to improve the aerodynamic performance of an H-type Darrieus wind turbine using an innovative fluidic flow control technique based on the synergistic effect of blowing and suction. The aeroacoustic noise emissions accomplished with this enhancement are evaluated. The Improved Delayed Detached Eddy Simulation turbulence model and the Ffowcs Williams-Hawkings acoustic analogy method are adopted to simulate the instantaneous flow field and predict the far field noise. Following validation of the numerical approach using wind tunnel experimental data on a static airfoil, an orthogonal experimental design method was used to analyze and optimize the operating factors. The factors include suction position relative to leading-edge ( L s ), blowing position relative to trailing-edge ( L b ) and jet coefficient ( C μ ). The results indicate that C μ plays crucial role in determining the airfoil performance, while the role of L b is almost negligible. Furthermore, the impact of optimal combination of these factors was analyzed based on three different control strategies. It is found that appropriate application of the active control solution can eliminate the wind turbine's negative torque, avoid excessive alternating load on the rotor and improve the energy extraction efficiency. The aeroacoustic noise estimation shows that the active device can reduce the noise emission by moderating pressure fluctuation, stabilizing the flow field and influencing the vortex shedding. Similarly, the proposed active control solution can reduce the wind turbine noise level by up to 6.56 dB by modifying the sound pressure spectra at frequencies between 100 and 1000 Hz.